Quantification of lectin fluorescence in GNE myopathy muscle biopsies. Issue 2 (23rd April 2018) - Leoyklang, Petcharat; Class, Bradley; Noguchi, Satoru; Gahl, William A; Carrillo, Nuria; Nishino, Ichizo; Huizing, Marjan; Malicdan, May Christine
ABSTRACT: Introduction : GNE myopathy is an adult‐onset muscle disorder characterized by impaired sialylation of (muscle) glycans, detectable by lectin histochemistry. We describe a standardized method to quantify (lectin‐) fluorescence in muscle sections, applicable for diagnosis and response to therapy for GNE myopathy. Methods : Muscle sections were fluorescently labeled with the sialic acid‐binding Sambucus nigra agglutinin (SNA) lectin and antibodies to sarcolemma residence protein caveolin‐3 (CAV‐3). Entire tissue sections were imaged in tiles and fluorescence was quantified. Results : SNA fluorescence co‐localizing with CAV‐3 was ∼50% decreased in GNE myopathy biopsies compared with muscle‐matched controls, confirming previous qualitative results. Discussion : This quantitative fluorescence method can accurately determine sialylation status of GNE myopathy muscle biopsies. This method is adaptable for expression of other membrane‐associated muscle proteins, and may be of benefit for disorders in which therapeutic changes in expression are subtle and difficult to assess by other methods. Muscle Nerve 58 : 286–292, 2018